Hungarian Monitoring, 6 April 1989 . [Magyar rádiófigyelő], 1989. április 6 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Gorbachev in England, interview with Thatcher - After the Polish roundtable talks, American opinions - Looking back at Gorbachev's Cuban visit - Academic Arbatov the victim of election fraud Domestic Affairs: - Ministerial council in session: exhumation of Imre Nagy and colleagues begins, public burial to be held on June 16 - Historical Justice Committee holds press conference - Interview with Mrs. Maléter - Planning committee session of Comecon countries opens in Budapest - Hungarian Foreign Ministry protests to Romanian embassy counselor after MTV reporters are denied entry to Romania - Hungarian Socialist Workers' Party (MSZMP) reform circle supports the Party leadership's intention to hold discussions - Gyula Horn speaks on orientation of Hungarian foreign policy - State of affairs at Gabčíkovo-Nagymaros construction Economy: - Production stops at Ikarusz, over 100 million production shortfalls per day - Austrian Chamber of Commerce estimates that Hungarians have spent approx. ATS 1 billion in Austria over the past few months Külpolitika: - Gorbacsov Angliában, Thatcher interjú - A lengyel kerekasztal tárgyalás után:, amerikai vélemény - Visszapillantás Gorbacsov kubai látogatására - Arbatov akadémikus választási csalás áldozata lett Belpolitika: - A Minisztertanács ülése: befejeződött Nagy I. és társai exhumálása, június 16-n lesz a nyilvános temetés - A Történelmi Igazságtétel Bizottság sajtóértekezletet tartott - Interjú Maléter Pálnéval - Budapesten megkezdődött a KGST országok tervegyeztető bizottságának ülése - A Magyar Külügyminisztérium tiltakozott a román nagykövetség tanácsosánál, amiért nem engedték be Románia területére az MTV forgatócsoportját - Az MSZMP reform-köre támogatja a párt vezetésének tárgyalási szándékát - A magyar külpolitikai orientációról beszél Horn Gyula - Állapotjelentés a bős-nagymarosi építkezésről Gazdaság: - Leáll a termelés az Ikaruszban, napi több, mint százmillió a termeléskiesés - Az Osztrák Kereskedelmi Kamara becslése szerint kb. 1 milliárd Schillinget költöttek a magyarok az elmúlt hónapokban Ausztriában